IB Theory and the entry of MNCs in Brazil from 1850 to 2007 - Amatucci, Marcos; Avrichir, Ilan (Review of Business Management, 2008)
This paper analyses the applicability of the main enterprise internationalization theories to the entry of the multinational corporations into Brazil, throughout five phases of Brazilian economy, from 1850 to nowadays. It seeks to verify the explanation power of each theory over the FDI flows in Brazil. It concludes that there is a contingency relation between the theories and the phases of the economy, and it shows such relationship in a table. In addition, it concludes that the most powerful theory along the researched period was Dunning’s eclectic paradigm, mainly due to the Localization considerations. Theoretical propositions are put forward as a contribution to future research. Key-words: International management. MNCs in Brazil. International business theory. Eclectic paradigm. Dunning.